Experimentally investigating the degradations of the GaN PA indexes under different temperature conditions. Issue 3 (18th September 2020) - Zhou, Shaohua
Abstract: In order to understand the PA's indexes, degradations with respect to the temperature changes before suppressing such degradations or compensating those temperature effects of the PAs. The degradations of the gallium nitride (GaN) PA indexes under different temperature conditions with a fixed relative humidity of 85% are investigated experimentally. The S21, power‐added efficiency (PAE) and output power of the PA degrade with the increase of the temperature. The main reasons for these degradations are discussed and analyzed in this paper. The results presented in the paper can help designers to understand the temperature effects on degradations of GaN PA indexes comprehensively so that the designers could consider the effects in the design cycle of the temperature compensation circuits in advance.